A MODERN LITERATURE REVIEW OF THE PROBLEM OF HIV ENCEPHALOPATHY - Zokirov Muzaffar (Modern American Journals, 2025)
This article provides an overview of current concepts of HIV-associated encephalopathy and HIV-associated dementia in the context of the spectrum of HIV-associated neurocognitive disorders (HAND). Epidemiological trends in the era of combination antiretroviral therapy are considered, and a shift from the classical AIDS- dementia complex to the prevalence of mild and moderate cognitive impairment is shown. Key mechanisms of neuropathogenesis are analyzed in detail, including early involvement of the central nervous system, the role of chronic neuroinflammation, blood-brain barrier dysfunction, viral proteins, and concomitant vascular and neurodegenerative pathology. The clinical features of HIV-associated encephalopathy and HIV-associated dementia, and current approaches to diagnostics using neuropsychological testing, neuroimaging, and biomarkers are discussed. Particular attention is paid to the impact of antiretroviral therapy, including integrase inhibitor-based regimens, as well as unresolved issues of adjuvant Neuroprotective treatment. The importance of early screening for cognitive impairment, an interdisciplinary approach, and the development of multimodal diagnostic models integrating clinical, neuroimaging, and laboratory data is emphasized.
Keywords: HIV encephalopathy; HIV-associated dementia; HIV-associated neurocognitive disorders (HAND); neuroinflammation; antiretroviral therapy; biomarkers; neuroimaging; cognitive impairment.